Development of interactive multimedia based mathematics learning media macromedia flash 8 - Sartika Putri; Abdurrahman Abdurahman; Dedek Andrian; Lilis Angraini; Leo Effendi (SAINTIS Publishing, 2022)
The development of interactive multimedia-based mathematics learning media using Macrome-dia Flash 8 is included in research and development. This study aims to produce learning media products based on Macromedia Flash 8 mathematics on the material similarity and congruence for grade IX junior high school students. This research refers to the development of ADDIE which includes five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The instruments used are media validation sheets and student response questionnaires. The data collection technique used is validity data by 3 validators consisting of 2 Lecturers of Mathematics Education and 1 Mathematics Teacher. The data analysis technique used is the analysis of the validity and practicality of the learning media. The results of the analysis of the average validity of learning media are 86.57% with very valid criteria, while the average practicality of learning me-dia is 89.53% with very practical criteria. Based on the results of research and development, it can be concluded that the learning media developed is suitable for use in learning mathematics.